O sus e a política nacional de promoção da saúde: perspectiva resultados, avanços e desafios em tempos de crise - Deborah Carvalho Malta (2018)
This article examines progress made towards the implementation of the core priorities laid out in the National Health Promotion Policy (PNPS, acronym in Portuguese) and current challenges, highlighting aspects that are essential to ensuring the sustainability of this policy in times of crisis. It consists of a narrative review drawing on published research and official government documents. The PNPS was approved in 2006 and revised in 2014 and emphasizes the importance of social determinants of health and the adoption of an intersectoral approach to health promotion based on shared responsibility networks aimed at improving quality of life. Progress has been made across all core priorities: tackling the use of tobacco and its derivatives; tackling alcohol and other drug abusepromoting safe and sustainable mobility; adequate and healthy food; physical ac tivity; promoting a culture of peace and human rights; and promoting sustainable development. However, this progress is seriously threatened by the grave political, economic and institutional crisis that plagues the country, notably budget cuts and a spending cap that limits public spending for the next 20 years imposed by Constitutional Amendment Nº 95, painting a future full of uncertainties.